TINGKAT ANSIETAS SISWA YANG AKAN MENGHADAPI UJIAN NASIONAL TAHUN 2016 DI SMA NEGERI 3 DENPASAR - Ni Wayan Eka Widyartini; Ni Ketut Sri Diniari (E-Jurnal Medika Udayana, 2016)
The burden of education is one of the major stressors in adolescence and young adulthood. The national examination for instance, often triggers anxiety in the students who will deal with it. Anxiety in students can be measured with one measuring instrument that has been validated in Indonesia, namely Depression Anxiety Stress Scale (DASS). This study aims to determine the level of anxiety in students who will face national exam in 2016 in SMA Negeri 3 Denpasar. This study is a cross-sectional study descriptive with data collection conducted on December 28, 2015 - January 4, 2016. A total of 76 respondents obtained 52 votes (68.4%) experienced anxiety and the remaining 24 (31.5%) normal. Of the 52 samples, 6 (11.5%) experienced very severe anxiety, 14 (26.9%) experienced severe anxiety, 19 (36.5%) had moderate anxiety, and 13 people (25%) experienced mild anxiety. Distribution anxiety level by sex obtained men who experience anxiety as many as 15 people (62.5%) and 9 (37.5%) did not. Men who suffer from mild anxiety as many as three people (12.5%), moderate anxiety 7 (29.1%), severe 3 (12.5%), and very severe 2 (8.3%). In women 48 people (92.4%) experienced anxiety while 4 (7.6%), others do not. Women who experience mild anxiety as many as 11 people (21.1%), moderate anxiety were 12 people (23%), severe anxiety 10 (19.2%), and very severe as many as 15 people (28.8%). Need to pay attention to not only the student's academic ability but also pay attention to the anxiety felt by students. It is important to deal with anxiety on students in an effort to improve student academic achievement.